PENGUKURAN KINERJA PEMERINTAH DAERAH KABUPATEN LAMONGAN BERDASARKAN KONSEP VALUE FOR MONEY - KHIKMAH, ALAYYAL (Jurnal Akuntansi AKUNESA, 2014)
This study is to measure the performance of Local Government Lamongan based concept of value for money, which includes economic, efficiency, and effectiveness. This study uses Lamongan financial statements five years between 2009 to 2013. The results show that the performance of the Regional Government of Lamongan uneconomical due to a rate of over 100%, meaning that the government is not successful in controlling the costs incurred and resulting in wasteful expenditure and unproductive. If viewed from the efficiency and effectiveness, the performance of the government has been efficient and effective. This means that the government has been able to manage financial resources well and succeed in determining the regional target revenue.Keywords: value for money, economic, efficiency, effectiveness